Pemberdayaan Masyarakat Dalam Peningkatan Produktifitas Pancake Durian di Gampong Kemuneng Hulu, Aceh Timur - Nanda Herijal Putra (Fakultas Ekonomi dan Bisnis Islam IAIN Langsa, 2023)
This program aims to increase the economic role of the community in the rural community of Keumuneng Hulu Village, East Aceh Regency. The service model used is the Participation Action Reasearch (PAR) method. Through a collaborative approach, the program provides training and assistance to women in various aspects of durian processing and marketing. The results obtained after community service was carried out showed that during one month there was a significant increase in both production and income. The average weekly production of durian pancakes per woman increased from 30 to 50-60 pieces, followed by an increase in weekly income from Rp 500,000 (five hundred thousand rupiah) to Rp 1,000,000 (one million rupiah) to reach 1,200,000 (one million two hundred thousand rupiah). This research emphasizes the importance of community participation in local economic development and showcases the potential of value-added processing to uplift rural economies. Thus, further support is expected from the government to continue to support in terms of capital assistance and further education to develop gender empowerment and community development, illustrating the real impact of collaborative efforts.